2023
DOI: 10.3390/ijms24020983
|View full text |Cite
|
Sign up to set email alerts
|

On Associations between Fear-Induced Aggression, Bdnf Transcripts, and Serotonin Receptors in the Brains of Norway Rats: An Influence of Antiaggressive Drug TC-2153

Abstract: The Bdnf (brain-derived neurotrophic factor) gene contains eight regulatory exons (I–VIII) alternatively spliced to the protein-coding exon IX. Only exons I, II, IV, and VI are relatively well studied. The BDNF system and brain serotonergic system are tightly interconnected and associated with aggression. The benzopentathiepine TC-2153 affects both systems and exerts antiaggressive action. Our aim was to evaluate the effects of TC-2153 on the Bdnf exons I–IX’s expressions and serotonin receptors’ mRNA levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…They found that male Bdnf -e1 −/− and e2 −/− mice displayed increased aggressive behavior compared with their wild-type littermates [ 10 ]. Interestingly, a recent study found higher expression levels of Exons I, II, III, V, VII, and VIII in the cortex of aggressive rats compared with tame ones [ 109 ], indicating that multiple Bdnf promoters may contribute to aggressive behaviors.…”
Section: The Function Of Bdnf Transcripts In Psych...mentioning
confidence: 99%
“…They found that male Bdnf -e1 −/− and e2 −/− mice displayed increased aggressive behavior compared with their wild-type littermates [ 10 ]. Interestingly, a recent study found higher expression levels of Exons I, II, III, V, VII, and VIII in the cortex of aggressive rats compared with tame ones [ 109 ], indicating that multiple Bdnf promoters may contribute to aggressive behaviors.…”
Section: The Function Of Bdnf Transcripts In Psych...mentioning
confidence: 99%